Dynamic compression response of self-reinforced polypropylene composite structures fabricated through ex-situ consolidation process. (15th November 2018) - Imran, Ali; Qi, Shijie; Yan, Chun; Liu, Dong; Zhu, Yingdan; Yang, Guilin
Graphical abstract: Abstract: In case of Self-reinforced polymer composites (SRCs) the fibres and matrix belong to the same family of polymers that can ensure 100% recyclability as compared to traditional fibre reinforced epoxy matrix based composites. Most of the SRCs were studied only on material bases not structural bases, although some structures were fabricated but most of their fabrication methods can hardly be applied for mass production. We fabricated self-reinforced polypropylene (SrPP) structures by ex-situ consolidation process that can be potentially applied for mass production. Instead of conventional stamping process that involves complex formability phenomenon; a mould was designed to fabricate corrugated core from the pre-consolidated SrPP sheets and then face sheets were joined by same family of polymer adhesives to achieve maximum recyclability. Optimal bending temperature was investigated to maintain proper fibre matrix contents of corrugated SrPP sheets. Interface between core and face sheet (FS) was enhanced through phenomenon of mechanical lock by creating various abrasion levels. Dynamic strengthening effect and collapse behaviour of structures during out of plane dynamic compression tests was investigated and compared with theoretical predictions.